COVID-19 and diabetes; Possible role of polymorphism and rise of telemedicine - Sayed, Shomoita (A pilot randomized controlled trial examining the feasibility, acceptability, and efficacy of Adapted Motivational Interviewing for post-operative bariatric surgery patients, 2021)
• Epidemiological studies conclude diabetes to be a leading comorbidity of COVID-19. • ACE2 polymorphisms in host can influence SARS-CoV-2 susceptibility or resistance. • The in-silico data need to be corroborated with in-vivo results. • Telemedicine can bring a new change in diabetes care.